Improving of ecological characteristics of technology on pyrolysis of scrap tires - Vovk, Oksana A.; Arhipova, Galina I.; Nikitchenko, Julia S. (Proceedings of National Aviation University (archive), 2009)
This article is devoted to the problem of looking for new alternative energy sources. Mutually beneficial integration of alternative energy searches with utilization of scrap tire is considered. Concerned processing line on scrap tires treatment is environment friendly and economically sound.